Characteristics of Irony and its Expression as a Component Part of Author Modality - Khamdamovna, Mavlonova Ugiloy; Yuryevna, Saakyan Roza (International Journal on Integrated Education, 2023)
This article discusses seven features of irony, two main socio-psychological factors contributing to its intensification. Theoretically, further development of the textual category of irony as an integral part of the author's modality is revealed. It is proved that irony is a multi-level ontological and epistemological phenomenon.